THE EFFECT OF 3D PRINTING MACHINE PARAMETERS IN EXTRUSION PROCESS OF BIOCOMPOSITE MATERIALS (PMMA AND HA) ON DIMENSIONAL ACCURACY - Raeshifa Diani Almy; Alva Edy Tontowi (Universitas Mercu Buana, 2018)
Bone implants are medical procedures involving replacement or reconstruction of missing or damaged bones with the patient's ones, natural substitutes or artificial substitutes. The widely used bone cement is a polymethylmethacrylate (PMMA) based composite material. To improve bioactivity, PMMA is combined with hydroxyapatite (HA). The manual formation can make bone implants during surgery. However, the method requires a longer operation time and raises the possibility of a higher error. Therefore, 3D printing technology is used to improve the quality of bone implants. One of the machines that can be used is the 3D printing machine, the property of the Product Design and Development Laboratory of Universitas Gadjah Mada. This machine needs to be tested to determine the accuracy of the prints, which is one indicator of product quality. Several machine parameters can be set in this machine setting. This study aims to determine the effect of three parameters, those are perimeter speed or edge print speed (20-40 mm / s), infill speed or inner print speed (50 - 70 mm / s), and fill angle or inner slope of inner printing (45 - 90 ° C). Before printing complex shapes, the machine was tested in advance with a more straightforward specimen design, which is a specimen design of flexural strength test. Response surface experiment design is used to determine the effect of three parameters on the dimensional accuracy which is measured through dimensional error. The results show that these three factors have no significant impact on the dimensional error, but the resulting error is still high. Therefore, it is necessary to adjust the design size before printing.